Environmental and Biological Factors Influencing Dispersal of Neonate Leatherback Turtles (Dermochelys coriacea) From an Endangered Costa Rican Nesting Population - Barbour, Nicole; Shillinger, George L.; Hoover, Aimee L.; Williamson, Sean A.; Coles, Victoria J.; Liang, Dong; Fagan, William F.; Bailey, Helen (Frontiers in Marine Science, 2020)
Quantifying early life movements is essential to understanding migratory pathways and habitat use that can impact individuals’ success later in life. To gauge how neonatal movements set the stage for later habitat use, we tracked neonate leatherback turtles (n=94) with acoustic tags from Pacuare, Costa Rica, in 2016 and 2018. We analyzed movements using a first passage time analysis and random walk models, the results of which indicated neonates followed a fixed compass direction as they traveled away from shore and that strong currents in these areas resulted in advection. We combined the tracking data with concurrent environmental variables in a generalized additive mixed model framework. Our results showed the south-east current flow in this area has spatial and temporal structure that was not driven by the tidal current or local wind speed. Accounting for advection by the currents, in-water neonate swimming speed was significantly related to current speed, first passage time, and the year. Neonates had three main response strategies to currents above 0.5 m s-1, with most increasing their swimming speed and the rest maintaining either a constant or decreased swimming speed. Neonates were significantly larger in 2018 than in 2016 but their average swimming speed was not significantly related to body size, indicating that environmental factors were more important contributors to their dispersal. We conclude that abiotic factors, including the strength and direction of the currents, significantly affect the swimming and dispersal strategy of neonate leatherback turtles and these results can help to inform strategies for releases of neonate turtles from hatcheries, future tracking studies, and conservation efforts.